2009
DOI: 10.1002/cbic.200900009
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Nacre: Biochemistry and Proteomics of the Shell Organic Matrix of the Cephalopod Nautilus macromphalus

Abstract: Matrix evolutions: We have biochemically characterized the nacre matrix of the cephalopod Nautilus macromphalus, in part by a proteomic approach applied to the acetic acid‐soluble and ‐insoluble shell matrices, as well as to spots obtained after 2D gel electrophoresis. Strikingly, most of the obtained partial sequences are entirely new, whereas a few correspond only partly with bivalvian nacre proteins. Our findings shed new light on the macroevolution of nacre matrix proteins. magnified imageIn mollusks, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 67 publications
8
75
0
Order By: Relevance
“…However, Vendrasco et al [9] concluded that nacre instead convergently evolved in early molluscs because: (1) there are no clear cases of nacre in molluscs from the early or middle Cambrian, in spite of much data on their shell microstructures; (2) there are differences in the microscopic form and growth method of nacre between modern molluscan classes; (3) the constituent proteins differ markedly between nacre-bearing molluscs [47]; (4) the genes associated with nacre vary among modern classes of mollusc [48]; and (5) many modern monoplacophorans have foliated (or semi-foliated) aragonite instead of or together with nacre in their inner shell.…”
Section: The Origin Of Nacrementioning
confidence: 99%
“…However, Vendrasco et al [9] concluded that nacre instead convergently evolved in early molluscs because: (1) there are no clear cases of nacre in molluscs from the early or middle Cambrian, in spite of much data on their shell microstructures; (2) there are differences in the microscopic form and growth method of nacre between modern molluscan classes; (3) the constituent proteins differ markedly between nacre-bearing molluscs [47]; (4) the genes associated with nacre vary among modern classes of mollusc [48]; and (5) many modern monoplacophorans have foliated (or semi-foliated) aragonite instead of or together with nacre in their inner shell.…”
Section: The Origin Of Nacrementioning
confidence: 99%
“…Briefly, the fraction was enzymatically digested with trypsin [57] and then purified with a Vivapure C18 micro membrane (Vivascience). The purified samples were analyzed by nano-LC-MS/MS with a nano-Liquid Chromatography system (LC Packings, Dionex) and a nano-ESI-qQ-TOF mass spectrometry system (QSTAR XL, AB Sciex).…”
Section: à3mentioning
confidence: 99%
“…Mass spectrometry data were acquired with use of Analyst QS 1.1 software (AB Sciex) operated in IDA mode as previously described. [57] Protein identification was performed with ProteinPilot 3.0 software (Applied Biosystems) with use of the Paragon database search algorithm and the sequence determined from the DNA sequencing.…”
Section: à3mentioning
confidence: 99%
“…Of those published, many have focused on bivalve species, such as marine mussels of the genus Mytilus (M. edulis, M. galloprovincialis, M. trossulus) that reside off the European coast. Most of the studies published have utilized proteomic analysis to examine taxonomic differences [42][43][44][45][46][47], heritability [48], and evolution of the nacre [49]. One of the first environmental toxicology proteomic studies with aquatic invertebrates was conducted on Mytilus.…”
Section: Aquatic Invertebratesmentioning
confidence: 99%